Non-escaping frost tolerant QTL linked genetic loci at reproductive stage in six wheat DH populations - Zhang, J.; Islam, MD S.; Zhao, Y.; Anwar, M.; Alhabbar, Z.; She, M.; Yang, R.; Juhasz, A.; Tang, G.; Chen, J.; Liu, H.; Jiang, Y.; et al. (Elsevier, 2021)
Reproductive stage frost poses a major constraint for wheat production in countries such as Australia. However, little progress has been made in identifying key genes to overcome the constraint. In the present study, a severe frost event hit two large-scale field trials consisting of six doubled haploid (DH) wheat populations at reproductive stage (young microspore stage) in Western Australia, leading to the identification of 30 robust frost QTL on 17 chromosomes. The major 18 QTL with the phenotype variation over 9.5% were located on 13 chromosomes including 2A, 2B, 2D, 3A, 4A, 4B, 4D, 5A, 5D, 6D, 7A, 7B and 7D. Most frost QTL were closely linked to the QTL of anthesis, maturity, Zadok stages as well as linked to anthesis related genes. Out of those, six QTL were repetitively detected on the homologous regions on 2B, 4B, 4D, 5A, 5D, 7A in more than two populations. Results showed that the frost damage is associated with alleles of Vrn-A1a, Vrn-D1a, Rht-B1b, Rht-D1b, and the high copy number of Ppd-B1. However, anthesis QTL and anthesis related genes of Vrn-B1a and TaFT3-1B on chromosomes 5B and 1B did not lead to frost damage, indicating that these early-flowering phenotype related genes are compatible with frost tolerance and thus can be utilised in breeding. Our results also indicate that wild-type alleles Rht-B1a and Rht-D1a can be used when breeding for frost-tolerant varieties without delaying flowering time.